Solution Structural Studies of GTP:Adenosylcobinamide-Phosphateguanylyl Transferase (CobY) from Methanocaldococcus jannaschii. - Kiran K Singarapu; Michele M Otte; Marco Tonelli; William M Westler; Jorge C Escalante-Semerena; John L Markley (PLoS ONE, 2015)
GTP:adenosylcobinamide-phosphate (AdoCbi-P) guanylyl transferase (CobY) is an enzyme that transfers the GMP moiety of GTP to AdoCbi yielding AdoCbi-GDP in the late steps of the assembly of Ado-cobamides in archaea. The failure of repeated attempts to crystallize ligand-free (apo) CobY prompted us to explore its 3D structure by solution NMR spectroscopy. As reported here, the solution structure has a mixed α/β fold consisting of seven β-strands and five α-helices, which is very similar to a Rossmann fold. Titration of apo-CobY with GTP resulted in large changes in amide proton chemical shifts that indicated major structural perturbations upon complex formation. However, the CobY:GTP complex as followed by 1H-15N HSQC spectra was found to be unstable over time: GTP hydrolyzed and the protein converted slowly to a species with an NMR spectrum similar to that of apo-CobY. The variant CobYG153D, whose GTP complex was studied by X-ray crystallography, yielded NMR spectra similar to those of wild-type CobY in both its apo- state and in complex with GTP. The CobYG153D:GTP complex was also found to be unstable over time.